Isolasi Bakteri Endofit Tanaman Pepaya (Carica Papaya L.) Dan Uji Aktivitas Enzim Amilase - Ginting, Ledy; Wijanarka, Wijanarka; Kusdiyantini, Endang (Berkala Bioteknologi, 2020)
ABSTRACTEndophytic bacteria are beneficial microorganisms that interact with plants without causing disturbance or damage to them. Research shows that certain endophytic bacterial isolates can produce secondary metabolites that have health effects, especially endophytic bacteria isolated from the Papaya plant (Carica Papaya. L). Amylolytic bacteria is one of the bacteria that has the potential to produce amylase enzymes which play an important role in industry. Endophytic bacteria were isolated using Nutrient Agar media 1% starch (soluble starch) and amylolytic index measurements were carried out using Lugol's reagent. Isolation of endophytic bacteria was carried out by streak method on Nutrient Agar media. The cultures were incubated at 37ºC for 48 hours. The morphological characteristics of the growing colonies were observed and Gram stained was carried out. Amylase activity was measured using the Dinitrosalisilic acid (DNS) method. The results of this study found 19 isolates of endophytic bacteria were isolated. There were 5 isolates that had the highest clear zone, namely isolates AE4, BE2, DE6, TD2, and TD5. The highest amylase enzyme activity of 0.225 U / mL was produced in TD5 isolates.Keyword : Isolation, Endophytic Bacteria, Enzyme Amylase, Papaya Plants